Research and Development in Intelligent Systems XXV Proceedings of AI-2008, the Twenty-eighth SGAI International Conference on Innovative Techniques and Applications of Artificial Intelligence - Bramer, Max.; Petridis, Miltos.; Coenen, Frans. (Springer London, 2009)
The papers in this volume are the refereed technical papers presented at AI-2008, the Twenty-eighth SGAI International Conference on Innovative Techniques and Applications of Artificial Intelligence, held in Cambridge in December 2008. They present new and innovative developments in the field, divided into sections on CBR and Classification, AI Techniques, Argumentation and Negotiation, Intelligent Systems, From Machine Learning To E-Learning and Decision Making. The volume also includes the text of short papers presented as posters at the conference. This is the twenty-fifth volume in the Research and Development series. The series is essential reading for those who wish to keep up to date with developments in this important field. The Application Stream papers are published as a companion volume under the title Applications and Innovations in Intelligent Systems XVI.